Genetics of aging in the fruit fly, Drosophila melanogaster. - Helfand, S.L.; Rogina, B. (Annual Review of Genetics, 2003)
Research into the mechanisms underlying the process of aging is emerging as an exciting area of biomedical research. Observations challenging the fundamental assumptions of aging have begun to rejuvenate the field, opening up aging research to fresh ideas and approaches. Genetic approaches, which have been successfully used to understand other complex biological phenomena, are beginning to reveal important patterns and conservations between the processes of aging in a variety of species including yeast, nematodes, flies, and mice. A combination of candidate and random gene alteration approaches, particularly in the fruitfly model system, Drosophila melanogaster, should prove to be especially valuable for elucidating the primary physiological systems involved in aging and life span determination.